A homonimy in Psyllidae (Homoptera): a new name for Neopelma Burckhardt - Straube,Fernando Costa (1999)
Burckhardtia nom. nov. is proposed for Neopelma Burckhardt, 1987 (Psyllidae, Homoptera), preoccupied by Neopelma Sclater, 1860 (Pipridae, Aves).